The Effectiveness of Guided Inquiry Model and Problem-Based Learning on Critical Thinking Skills of Elementary School Students - Jenny Indrastoeti Siti Poerwanti; Ahmad Syawaludin; Sri Marmoah (Universitas Pendidikan Ganesha, 2022)
The teaching and learning process is still focused on educators. Students are less willing to accept learning materials and social studies. Therefore, students only have a correct understanding of the material. This research is an experimental study that uses a pre-test-post-test design with experimental and control classes. This study aims to analyze the differences in critical thinking abilities of elementary school students in the experimental class with the problem-based learning model and the control class using the guided inquiry learning model. The population in this study was fourth-grade students. The sampling technique using stratified cluster random sampling was chosen as the sampling technique. Data processing is done by analyzing Paired Sampling and Independent Sampling. The results showed (1) the t-test analysis obtained two-sided Sig of 0.00 <0.05, the hypothesis Ho was rejected, and there were differences in the effectiveness of using the PBL model and learning guidelines on student criticality. social studies thinking skills, (2) The calculation of effect size shows that the problem-based learning model (PBL) is more effective than the guided inquiry model on students' critical thinking skills in social studies learning. The critical thinking skills of students who use the problem-based learning model are much higher than the critical thinking skills of students who use the guided inquiry model. The problem-based learning (PBL) model is more effective than the guided inquiry model for social studies learning about students' critical thinking skills that can analyze and solve their problems.